PENDAMPINGAN MASYARAKAT DALAM UPAYA MENINGKATKAN NILAI JUAL PRODUK ASLI WIRAUSAHA KECAMATAN PEMULUTAN - Ikbal Barlian; Dewi Koryati; Rusmin AR; Deskoni; Dewi Pratita (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2017)
This study discusses the activities of community assistance in an effort to increase the selling value of the original products of entrepreneurs in the district of Pemulutan. The formulation of the problem in this study is “how the effort in preparing and creating a work plan to increase the selling value of the original products of entrepreneurs in Disctict Pemulutan? And how the tips that can be done in the effort to compose and create a work plan to increase the selling value of the original product entrepreneur in District of Pemulutan?”. This research is a study of community service. The type of activities undertaken in this study is the provision of knowledge in an effort to develop and create a work plan to increase the selling value of entrepreneurial products in the district of Pemulutan. Models that will be tested in this research is counseling in the form of giving material, guided and independent training in effort to compile and make work plan to increase the selling value of original product of entrepreneur in sub district of Pemulutan. Data collection techniques used a questionnaire filled out by the participants after following the extension activity. The results of questionnaire analysis obtained as much as 90% of participants get benefits after following the extension activities and they are interested in following extension activities.